1970
DOI: 10.1002/pssa.19700010217
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of hardness of titanium carbide in the homogeneity range

Abstract: Hardness investigations of titanium carbide are made in the homogeneity range from room temperature to 2270 °K. It is found that the hardness decreases with decreasing carbon content in the carbide. Activation energies of dislocation movement according to the Peierls‐Nabarro mechanism of plastic deformation are determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

1973
1973
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 3 publications
2
8
0
Order By: Relevance
“…11). The results for series A, B and C nearly coincide and the average value observed for the microhardness is only a little higher than reported for TiCx with the same carbon to metal ratio, x [2][3][4][5].…”
Section: 3 Microhardnesssupporting
confidence: 73%
See 2 more Smart Citations
“…11). The results for series A, B and C nearly coincide and the average value observed for the microhardness is only a little higher than reported for TiCx with the same carbon to metal ratio, x [2][3][4][5].…”
Section: 3 Microhardnesssupporting
confidence: 73%
“…This serves to explain why the hardness near the free surface of the coating is higher than near the coating/substrate interface. It is noted, however, that the hardness of TiCx increases with increasing carbon to metal ratio, x [2][3][4][5]. In the present case x decreases slightly with increasing distance to the coating/substrate interface (Fig.…”
Section: 3 Microhardnessmentioning
confidence: 54%
See 1 more Smart Citation
“…[1][2][3][4] Many investigations concerning the effect of χ on deformation behavior of TiC χ at high temperature have been made so far. Samsonov 5) reported that the Vickers hardness of sintered polycrystalline TiC χ with χ from 0.73 to 0.94 decreases with decreasing χ over the temperature range room temperature to 2270 K. Spivak 6) carried out the high temperature creep test for hot-pressed polycrystalline TiC χ , 0.63 ≤ χ ≤ 0.96, at very high temperature from 2370 to 2870 K and showed that the creep rate takes a minimum around χ = 0.9. And Miracle 7) conducted Vickers hardness, four point bending and compression tests for hot pressed polycrystalline TiC χ having χ from 0.66 to 0.93 at temperature from room temperature to 1470 K and showed that the strength decreases with decreasing χ.…”
Section: Introductionmentioning
confidence: 99%
“…In these samples, and appreciable content of impurities is usually included and the impurities are liable to form second phases of low melting point at grain boundaries, [8][9][10] thereby causing grain boundary sliding at relatively lower temperature which is different from the intrinsic mechanical properties of TiC χ . [4][5][6] Further around pores stress concentration occurs depending on the size and shape of pores. In short, for sintered TiC χ the effects of impurities, grain boundaries and pores on the mechanical properties are significant.…”
Section: Introductionmentioning
confidence: 99%